Etnobotânica, agroecologia e modelos alternativos em horticultura: análise de conteúdo da mídia impressa - Oliveira, Kleber Andolfato de [UNESP] (2015)
The outlined object to the focus of this project is part of the Globo Rural magazine of 001de editions September 1985 to 350 in December 2014. The proposal then is to analyze the critical point of view the speech as engender the type of print media as well as the visuals around themes relating to agriculture, in the case of this work of Ethnobotany, Agroecology and alternative models of Horticulture. To this end, this study contributes as a share to the development of an interpretive research into the discursive and media relations that the post-modern man builds with the different social, cultural and historical practices. The approach of the study is qualitative and quantitative, in which the researcher seeks to interpret the visual and discursive data materialized in editions of the magazine Globo Rural through content analysis proposed by Bardin. Bardin content analysis consists of a set of methodological nature of instruments constantly improving, which apply to speeches (content and continents) extremely diverse. In the analyzes of the primary or secondary headlines concerning the subject of Horticulture are largely related to a farming model currently questioned and in many cases the overlapping science. This conventional model called dominates the discourse and next to it an economic character arises in order to build a type of agriculture that not so suited to alternative models as proposed by this work